Clinical Course and Outcomes among COVID-19 Patients at the Hospitel in Bangkok: A Retrospective Study - Jackrapong Bruminhent; Yosapan Kaewsanga; Werapoj Jiraaumpornpat; Vanlapa Arnuntasupakul; Thitiporn Suwatanapongched; Sasisopin Kiertiburanakul (Tropical Medicine and Infectious Disease, 2022)
A hospitel is a hotel that has been designated as an extension of the healthcare facilities during the COVID-19 pandemic in resource-limited settings. However, the clinical course and outcomes of patients with COVID-19 admitted to this unique type of facility have never been studied. We retrospectively reviewed the medical records of adult patients with COVID-19 who were admitted to a single hospitel in Bangkok, Thailand. Risk factors with respect to chest X-ray progression and clinical progression were analyzed using a logistic regression. A total of 514 patients were recruited, with a mean (standard deviation) age of 35.6 (13.4) years, and 58.6% were women. Patients were admitted after a median (interquartile range) of 3 (2–6) days of illness and were classified with mild (12.3%), moderate (86.6%), and severe (1.1%) conditions. Favipiravir and corticosteroids were prescribed in 26.3% and 14.9% of patients, respectively. Chest X-ray progression was found in 7.6% of patients, and hospital transfer occurred in 2.9%, with no deaths. Favipiravir use (odds ratio (OR) 3.3, 95% confidence interval (CI) 1.4–7.5, p = 0.005), nausea/vomiting after admission (OR 32.3, 95% CI 1.5–700.8, p = 0.03), and higher oxygen saturation on admission (OR 1.99; 95% CI 1.22–3.23, p = 0.005) were factors associated with chest X-ray progression. Additionally, an oxygen requirement on admission was an independent risk factor for hospital transfer (OR 904, 95% CI 113–7242, p < 0.001). In a setting where the hospitel has been proposed as an extension facility for patients with relatively non-severe COVID-19, most patients could achieve a favorable clinical outcome. However, patients who require oxygen supplementation should be closely monitored for disease progression and promptly transferred to a hospital if necessary.